Sosialisasi Program Menghafal Al-Qur’an Sebagai Penerapan Pendidkan Non Formal Di Pondok Tahfadzul Qur’an Ar-Rifa’iyyah Langkat - Angellia Ramona Park; Liza Amelia Sari; Dwi Kurnia Rahayu (Fusion: Jurnal Pengabdian kepada Masyarakat, 2024)
The aim of the Al-Quran memorization program at Pondok Tahfadzul Qur'an Ar-Rifa'iyyah Langkat is to understand the learning process of the Qur'an tahfidz program as non-formal education in remote areas. The method of implementing activities with four stages, namely preparation, implementation of activities, and evaluation. The result of community service activities is that the application of the Al-Quran memorization program method at the Tahfadzul Qur'an Ar-Rifa'iyyah Langkat Islamic Boarding School or tahfiz house is to repeat memorizing the Qur'an. there is intensive guidance for students, giving students time to memorize the Koran, repeating (murojaah) memorizing the Koran. Many methods have been developed to memorize the Qur'an, but each method must be adapted to the conditions and situation. The method can also provide assistance to memorizers to reduce their difficulties in memorizing the Koran. Memorizing the Koran has a good effect on developing basic skills in students, and can improve education and academic achievement.